2019
DOI: 10.1021/acs.iecr.9b02360
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyl-Mediated Formation of Highly Dispersed SnO2/TiO2 Heterojunction via Pulsed Chemical Vapor Deposition To Enhance Photocatalytic Activity

Abstract: Engineering a heterojunction on a TiO 2 surface (such as SnO 2 /TiO 2 ) is an effective strategy to enhance photocatalytic activity, by facilitating charge separation. However, the traditional fabrication for heterojunctions is usually operated in an aqueous environment, with the drawback of homogeneous nucleation of SnO 2 , which lowers photocatalytic efficiency. Herein, we develop a low-temperature pulsed chemical vapor deposition method that dispersedly deposits SnO 2 on anatase TiO 2 . By regulating the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…[14][15][16][17][18] After coupling with light-responsive materials, the photogenerated electrons more easily flow into the SnO 2 side owing to its relatively strong electron-enrichment capability with a conduction band (CB) potential of −0.15 eV versus normal hydrogen electrode (NHE), based on energy band theory. [19,20] This result will greatly accelerate the electrochemical reactions, and meantime effectively avoid the electron-hole recombination. [21] Therefore, the SnO 2 anode hybridized with light-responsive materials is the promising solution and highly desirable for further improving its energy density to theoretical value.…”
mentioning
confidence: 99%
“…[14][15][16][17][18] After coupling with light-responsive materials, the photogenerated electrons more easily flow into the SnO 2 side owing to its relatively strong electron-enrichment capability with a conduction band (CB) potential of −0.15 eV versus normal hydrogen electrode (NHE), based on energy band theory. [19,20] This result will greatly accelerate the electrochemical reactions, and meantime effectively avoid the electron-hole recombination. [21] Therefore, the SnO 2 anode hybridized with light-responsive materials is the promising solution and highly desirable for further improving its energy density to theoretical value.…”
mentioning
confidence: 99%
“…128 Yu et al employed the CVD method to prepare the SnO 2 /TiO 2 heterostructure with a thickness of 810 nm. 161 Zhang et al synthesized high yields of SnO 2 nanobelts by water-assisted CVD technique. The belt-like morphology of SnO 2 showing the tetragonal rutile phase and length of 10 microns were prepared at 850 1C.…”
Section: Synthesis Of Nanostructured Snomentioning
confidence: 99%
“…17,18 Immobilizing TiO 2 on supportive catalysts has been conducted in many studies and has shown promising findings. 19 Different coating methods can be used for coating the photoelectrodes by TiO 2 catalysts, including electrodeposition, 20 sol−gel, 21−24 sol−spray, 25 chemical vapor deposition, 26 thermal treatment, 27 and hydrothermal treatment. 28 The fabrication and morphologies of TiO 2 have been investigated in various studies through zero-dimensional (0D), one-dimensional (1D), two-dimensional (2D), and threedimensional (3D) nanostructures.…”
Section: ■ Introductionmentioning
confidence: 99%
“… Titanium dioxide (TiO 2 ) is one of the most favorable catalysts that has been examined in various experimental studies for its resistivity to corrosion hasty. , It is considered a promising catalyst that could be used in visible light. , Immobilizing TiO 2 on supportive catalysts has been conducted in many studies and has shown promising findings . Different coating methods can be used for coating the photoelectrodes by TiO 2 catalysts, including electrodeposition, sol–gel, sol–spray, chemical vapor deposition, thermal treatment, and hydrothermal treatment . The fabrication and morphologies of TiO 2 have been investigated in various studies through zero-dimensional (0D), one-dimensional (1D), two-dimensional (2D), and three-dimensional (3D) nanostructures .…”
Section: Introductionmentioning
confidence: 99%